African Farm/Family Forestry and Producer Organizations for improved livelihoods and sustainable landscape management - Tieguhong, J.C.; Schure, J. (2015)
The paper tries to provide answers to questions on the status of farm/family forestry in Africa in terms of opportunities and challenges, their contribution to economic development and sustainable landscape management. In the paper, highlights are made on issues related to land tenure, institutional settings and other supporting policies. In addition, market access and factors that may influence the development of forest products value chains are discussed alongside the possibilities for promoting and strengthening cohesive actions amongst FFPOs in different countries and regions. Answers are provided on questions related to easiness to group formation and registration and their product base. Examples of such groups in terms of associations or federations at local, national and regional levels alongside some examples are briefly described. Information on how FFPOs are currently helping forestry farmers are provided with some examples clearly started including their future potentials and/or pitfalls. At the end of the paper, the outlook in the coming 5 to 10 years for the main opportunities and challenges awaiting farm/family forestry and related FFPOs in Africa are pinpointed.